An analysis of the population of Cryptococcus neoformans strains isolated from animals in Poland, in the years 2015–2019 - Magdalena Florek (Nature Portfolio, 2021)
Abstract Fungi belonging to the Cryptococcus neoformans/C. gattii species complex (CNGSC) are pathogens causing severe infections in humans and animals, that for humans may result in a mortality rate ranging up to 70%. The CNGSC is divided into eight major molecular types, that may differ in their virulence and susceptibility. In order to fully understand the epidemiology of cryptococcosis, it is important to study the world distribution and population structure of these pathogens. The present study is the first presenting a population of strains isolated in Poland and one of the few using a multi-species animal group as a source of the specimen. The pathogen was present in 2.375% of the tested animals. The URA5-RFLP and MALDI-TOF MS analyses have revealed that the population consisted exclusively of C. neoformans strains, with a predominance of major molecular type VNIV (C. neoformans var. neoformans). The MALDI-TOF MS was used to perform the CNGSC strains identification on both the species and sub-species level. Despite the fact that the animals providing the specimens were not treated with 5-fluorocytosine, around 10% of the tested population presented MIC values exceeding 64 mg/L, indicating the existence of the 5-fluorocytosine-resistant strains in the environment.